The degree to which citizenship values ​​are included in social studies curricula in the post-basic education for grades (11- 12) in the Sultanate of Oman - Al- Karusi, Sultan Kamis; Murad, Tahrawi Ramadan (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the degree of inclusion of citizenship values ​​in the curricula of social studies in the post-basic education stage for grades (11- 12) in the Sultanate of Oman. The descriptive approach was employed in this study through a content analysis form consisting of (48) terms distributed in three main areas: Political values, Economic values, and Social values. Results showed that the degree of inclusion came between medium and low. Political values ​​came as the highest repetitive sum reached (1239) times (36.6%) and with an average degree of inclusion. Moreover, social values ​​came in second place with a repeating total amounted of (1014) times (33.4%) and with an average degree of inclusion. However, the economic values ​​came in the third rank with a frequency total of (1132) times and a percentage of (30%) with a low degree of inclusion. Regarding the extent of the values ​​among the curricula of the two grades (11&12), the twelfth-grade curricula came as the highest degree of inclusion with a repetitive total of (1771) and a percentage of (52.3%), while the curricula of the eleventh grade came in second place and with a repetitive total of (1614) and a ratio of (47,7%). In the conclusion of the study, the researchers presented a set of recommendations and proposals that may contribute to enhancing the values ​​of citizenship in the curricula of social studies in the Sultanate of Oman.
Keywords: citizenship values; social studies curricula; post- basic education; Sultanate of Oman